2012
DOI: 10.4137/cmc.s9789
|View full text |Cite
|
Sign up to set email alerts
|

Stenosis of a Reconstructed Aorta Caused a Paradoxical Diastolic Pressure Gradient after Norwood Operation

Abstract: An infant with hypoplastic left heart syndrome showed paroxysmal episodes of bradycardia, hypotension, and hypoxemia upon crying after modified Norwood operation. Echocardiography showed decreased right ventricular ejection with grade III tricuspid regurgitation, a markedly enlarged aortic arch, and accelerated blood flow distal to the enlarged aorta. Aortography demonstrated an aneurysmal neo-aorta with an apple-shaped appearance. The pressure measurements revealed intriguing aortic hemodynamics: the diastoli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
1
0
0
Order By: Relevance
“…Importantly, our study demonstrated that increased heart rates, increased aortic stiffness, and aortic size discrepancy (smaller neoaorta relative to the native descending aorta) were independent determinants of reduced SEVR. Although heart rates were not specifically increased in Norwood patients (Table 1), increased aortic stiffness and aortic size discrepancy were rather specifically observed in our Norwood patients and have also been reported in several previous studies [21][22][23]. Voges and colleagues [24] reported that increased aortic stiffness in HLHS patients who underwent a Norwood procedure correlated with the amount of fibrosis and scarred tissue assessed by late gadolinium enhancement in magnetic resonance imaging.…”
Section: Reduced Sevr In Norwood Patients and Its Determinantssupporting
confidence: 85%
“…Importantly, our study demonstrated that increased heart rates, increased aortic stiffness, and aortic size discrepancy (smaller neoaorta relative to the native descending aorta) were independent determinants of reduced SEVR. Although heart rates were not specifically increased in Norwood patients (Table 1), increased aortic stiffness and aortic size discrepancy were rather specifically observed in our Norwood patients and have also been reported in several previous studies [21][22][23]. Voges and colleagues [24] reported that increased aortic stiffness in HLHS patients who underwent a Norwood procedure correlated with the amount of fibrosis and scarred tissue assessed by late gadolinium enhancement in magnetic resonance imaging.…”
Section: Reduced Sevr In Norwood Patients and Its Determinantssupporting
confidence: 85%